Mapping The Risk Levels and Distribution of Dengue Fever (Df) in The City of Pontianak Using Choropleth Maps and Point Mapping - Ghaliq Candri Haki; Rachmat Wahid Saleh Insani; Barry Ceasar Octariadi (International Journal of Science and Environment (IJSE), 2026)
Dengue Hemorrhagic Fever (DHF) remains a critical public health challenge in tropical regions, with Indonesia recording approximately 143,000 cases in 2022 alone, yet most local health authorities lack spatially explicit decision-support tools. This study aimed to design and develop a web-based Geographic Information System (GIS) capable of mapping DHF vulnerability levels and case distribution in Pontianak City, West Kalimantan, in real time. A research and development approach was employed, involving field observation, structured interviews with Pontianak City Health Office officials, and secondary data collection comprising 120 confirmed DHF patient records obtained from the health office for the period 2024 to May 2025. The system integrated real-time environmental data retrieved via the OpenWeatherMap API alongside population density data from the Central Bureau of Statistics (BPS). Vulnerability levels were calculated using a scoring method applied to four parameters — air temperature, rainfall, humidity, and population density — and visualized through dual-layer spatial techniques: Choropleth Maps to represent sub-district vulnerability gradations and Point Mapping to display precise case locations based on patient geographic coordinates. System validation was conducted through Black Box Testing, which confirmed full functional compliance, and User Acceptance Testing (UAT) with health office representatives, yielding a Strongly Agree score of 88.23%. The developed system successfully classified DHF vulnerability into three categories (High, Moderate, Low) and provided interactive, real-time spatial visualization, offering the Pontianak City Health Office a data-driven instrument for targeted DHF prevention and control.